Primary Tuberculosis of the Tonsil - Sood, AS; Bhardwaj, B; Gill, JS (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 17-18 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6798